Analysing (in)justice in the interplay of urbanisation and transport: The case of agrarian extractivism in the region of Urabá in Colombia - Toro López, Maritza; Van den Broeck, Pieter (Quaestiones Geographicae, 2021)
Infrastructural design, transport and mobility policies are strong instruments for interpreting historical urban and regional transformation processes. The paper addresses the intercausalities between both of them. To do so, it briefly sketches debates on the causalities of transport infrastructure and urbanisation and the theory of technological politics, drawing attention to the relationship between transport infrastructure and politics, and how infrastructures and their techno-political frames include means of power and authority. From there, the paper moves to the debate on the relationship between social justice and transport, showing how transport systems embody social processes and social (in)injustice. The history of agrarian extractivism in the region of Urabá in Colombia serves as a case study. The paper shows how existing transport networks of the region of Urabá have supported the expansion of agrarian extractivist industries and more specifically the production of transport (in)justice. It explores the development of the infrastructural network, transport systems and urbanisation of this region from the early 1900s onwards. Results show how the actual agrarian extractivist industries of the region are causing huge challenges related to the overlapping of transport scales, congestion and risks of accidents in urban areas, and how actual transport dynamics in the region are affecting urban development, generating a high segregation characterised by uneven distributions of public services and transport infrastructures. The paper reveals that the existing transport developments in the region of Urabá have no support for local development and are mainly thought for the efficiency of agrarian extractivist industries over local economic development. Agrarian extractivism has been a consistent factor in the economic, political and social spheres, and since colonial times the appropriation of natural resources and the dispossession of territories has been omnipresent. This paper explores the historical role of transport in agrarian extractivism, the long-term impact of the prolongation of old mechanisms, and the interrelations of the latter with current urbanisation and development. It con- cludes that infrastructural developments in this region have supported agrarian extractivist industries, first in colonial times, but also more recently, showing the deep embeddedness of the relation between mobility and urbanity in the (agrarian extractivist) development history of this region